Sintaro Gold Ground Coffee Business in Rejang Lebong Based on Financial Aspects and Sensitivity Analysis - Hidayat, Lukman; Koto, Hidayat; Hendratno, Tri; Fitri, Aidil (Badan Penerbitan Fakultas Pertanian (BPFP), 2024)
Sintaro Gold is one of the small and medium industries in the Rejang Lebong district, processing coffee into ground coffee. The development of this industry requires a financial feasibility analysis to see whether the business can provide profits and maximize the existing production process. The research aims to determine the financial aspects and sensitivity of the Sintaro Gold industry in producing ground coffee in Rejang Lebong. The research uses primary and secondary data with a quantitative descriptive approach. The financial aspect study uses calculations of the R-C Ratio (R/C), Net Present Value (NPV), Internal Rate of Return (IRR), and Net Benefit Cost Ratio (Net B/C) The sensitivity analysis is based on increases in raw material prices and decreases in selling prices. The results of the research found that at a discount factor level of 7.05%, the R/C was 1.56-2.40, the NPV was IDR 6,844,209, the Net B/C was 1.071 and the IRR was 9.07% so that this business worth developing. An increase in raw material prices of 3.61% is not sensitive to business, but a decrease in selling prices of 3.61% is sensitive to business feasibility.